Selected ethno-medicinal plants from Kenya with in vitro activity against major African livestock pathogens belonging to the “Mycoplasma mycoides cluster” - Kama-Kama, F.; Midiwo, Jacob; Ng'ang'a, J.; Maina, N.; Schieck, Elise G.; Omosa, L.K.; Osanjo, G.; Naessens, Jan (Elsevier, 2016)
Members of ‘Mycoplasma mycoides cluster’ are important ruminant pathogens in Africa. Diseases caused by these Mycoplasma negatively affect the agricultural sector especially in developing countries through losses in livestock productivity, mortality and international trade restrictions. There is therefore urgent need to develop antimicrobials from alternative sources such as medicinal plants to curb these diseases. In Kenya smallholder farmers belonging to the Maasai, Kuria and Luo rely on traditional Kenyan herbals to treat respiratory symptoms in ruminants. In the current study extracts from some of these plants were tested against the growth of members of Mycoplasma mycoides cluster.